84‐4: Invited Paper: Near‐Infrared Organic Upconversion Device with High Image Sensing Quality. Issue 1 (30th May 2018) - Liu, Shun-Wei; Biring, Sajal; Li, Ya-Ze; Wong, Ken-Tsung
Abstract : A novel up‐conversion device for NIR image sensing is proposed by integrating the OLED, OPV, and transparent electrodes. The proposed device captures NIR light reflected from the object and forms a real‐time image at the visible wavelengths on the OLED display with the image quality of > 600 dpi.